Recent progress in experimental studies on the catalytic mechanism of cytochrome c oxidase - Shimada, Atsuhiro; Tsukihara, Tomitake; Yoshikawa, Shinya (Frontiers in Chemistry, 2023)
Cytochrome c oxidase (CcO) reduces molecular oxygen (O2) to water, coupled with a proton pump from the N-side to the P-side, by receiving four electrons sequentially from the P-side to the O2-reduction site—including Fea3 and CuB—via the two low potential metal sites; CuA and Fea. The catalytic cycle includes six intermediates as follows, R (Fea32+, CuB1+, Tyr244OH), A (Fea32+-O2, CuB1+, Tyr244OH), Pm (Fea34+=O2-, CuB2+-OH-, Tyr244O•), F (Fea34+=O2-, CuB2+-OH-, Tyr244OH), O (Fea33+-OH-, CuB2+-OH-, Tyr244OH), and E (Fea33+-OH-, CuB1+-H2O, Tyr244OH). CcO has three proton conducting pathways, D, K, and H. The D and K pathways connect the N-side surface with the O2-reduction site, while the H-pathway is located across the protein from the N-side to the P-side. The proton pump is driven by electrostatic interactions between the protons to be pumped and the net positive charges created during the O2 reduction. Two different proton pump proposals, each including either the D-pathway or H-pathway as the proton pumping site, were proposed approximately 30 years ago and continue to be under serious debate. In our view, the progress in understanding the reaction mechanism of CcO has been critically rate-limited by the resolution of its X-ray crystallographic structure. The improvement of the resolutions of the oxidized/reduced bovine CcO up to 1.5/1.6 Å resolution in 2016 provided a breakthrough in the understanding of the reaction mechanism of CcO. In this review, experimental studies on the reaction mechanism of CcO before the appearance of the 1.5/1.6 Å resolution X-ray structures are summarized as a background description. Following the summary, we will review the recent (since 2016) experimental findings which have significantly improved our understanding of the reaction mechanism of CcO including: 1) redox coupled structural changes of bovine CcO; 2) X-ray structures of all six intermediates; 3) spectroscopic findings on the intermediate species including the Tyr244 radical in the Pm form, a peroxide-bound form between the A and Pm forms, and Fr, a one-electron reduced F-form; 4) time resolved X-ray structural changes during the photolysis of CO-bound fully reduced CcO using XFEL; 5) a simulation analysis for the Pm→Pr→F transition.